Optimum planting time and row spacing for bergamot mint (Mentha citrata Ehrh.) var. 'Kiran' under sub tropical plains of central Uttar Pradesh - Saini, Man Singh, V P Singh, Saudan Singh, P (Journal of Spices and Aromatic Crops, 2003)
A field experiment was conducted at CIMAP farm, Lucknow during 1997-98 to find out the optimum planting time and row spacing for newly developed variety JKiran' of bergamot Inint (Mentha citrata Ehrh.). The crop planted on 15 and 30 December produced higher total herb yield (356 and 349 q ha-1) but maximum oil yield (167 kg ha-1 )was obtained from 30 January planting. Planting at a closer row spacing of 45 or 60 cm produced higher herb and oil yield than wider row spacing of 75 cm. Planting of bergmnot mint in the end of January at a row spacing of 60 cm is suggested for maximum oil production from crop grown for two harvests. However, for a single harvest, planting in mid February is suggested to enable the farmers to grow bergamot mint in rotation with winter season crops such as potato, mustard and vegetables and also rainy season crops after the harvest of bergamot mint.